Diagnosis and management of ocular motility disorders - Ansons, Alec M.; Davis, Helen (Chichester, West Sussex ; Hoboken, New Jersey : Wiley, 2014)
This comprehensive, clinically-grounded textbook, now in its fourth edition, supports orthoptists and ophthalmologists in decision-making through the patient care process, from presentation to discharge. Written by authors with extensive experience in teaching and research, Diagnosis and Management of Ocular Motility Disorders offers a clear and practical overview of assessment and management principles and further explores the clinical features of specific disorders, from amblyopia and infantile strabismus to supranuclear and infranuclear disorders, as well as other miscellaneous disorders.
Results of amblyopia treatment Compliance; 11 Introduction to Concomitant Strabismus; Classification; Aetiology; Investigation; Management; 12 Esotropia; Classification; Primary esotropia; Consecutive esotropia; Secondary (sensory) esotropia; Residual esotropia; 13 Exotropia; Classification; Primary exotropia; Consecutive exotropia; Secondary (sensory) exotropia; Residual exotropia; 14 Infantile Strabismus and Dissociated Strabismus Complex; Classification; Prevalence; Infantile esotropia; Dissociated strabismus complex (DSC); 15 Microtropia and Allied Conditions.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (ebrary, viewed December 9, 2013).
Keywords: Eye -- Movement disorders; Eye -- Movements; Eye -- Movement disorders; Eye movements; Ocular motility disorders -- Diagnosis; Oculomotor muscles -- Physiopathology; MEDICAL -- Surgery -- General; Eye -- Movements; Eye -- Movement disorders; Ocular Motility Disorders -- diagnosis; Eye Movements; Ocular Motility Disorders -- therapy; Oculomotor Muscles -- physiopathology; Electronic books; Electronic books